2007
DOI: 10.1016/j.febslet.2007.10.025
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that the C‐terminal PB2‐binding region of the influenza A virus PB1 protein is a discrete α‐helical domain

Abstract: The influenza A virus RNA-dependent RNA polymerase is a heterotrimer composed of PB1, PB2 and PA subunits and essential for viral replication. However, little detailed structural information is available for this important enzyme. We show by circular dichroism spectroscopy that polypeptides from the C-terminus of PB1 that are capable of binding efficiently to PB2 fold into stable a-helical structures. Structure prediction analysis of this region of PB1 indicates that it likely consists of a three-helical bundl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 40 publications
(70 reference statements)
2
27
0
Order By: Relevance
“…3), a finding suggestive of an interaction with one or more nuclear resident viral proteins other than PA. In addition to PA, PB1 is known to interact with PB2, NP, PB1-F2, and itself (7,13,23,30), and while the location of homooligomerization, PB1-F2-and NP-binding domains are not known, the N40 polypeptide certainly contains the primary PB2 interaction site (19,35,39,43). Consistent with this, FRAP analysis of GFP-tagged versions of PB2 and the polymerase trimer indicated an interaction with N40 in the nucleus of cells (Fig.…”
Section: Discussionsupporting
confidence: 57%
“…3), a finding suggestive of an interaction with one or more nuclear resident viral proteins other than PA. In addition to PA, PB1 is known to interact with PB2, NP, PB1-F2, and itself (7,13,23,30), and while the location of homooligomerization, PB1-F2-and NP-binding domains are not known, the N40 polypeptide certainly contains the primary PB2 interaction site (19,35,39,43). Consistent with this, FRAP analysis of GFP-tagged versions of PB2 and the polymerase trimer indicated an interaction with N40 in the nucleus of cells (Fig.…”
Section: Discussionsupporting
confidence: 57%
“…The short peptide PB1 731-757 is able to disrupt the interaction between PB1c and PB2n A previous deletion study has suggested the involvement of PB1 in the assembly of PB1c and PB2n [22,24]. In the present study, we tested whether the standalone short peptide PB1 731-757 derived from H5N1 (A/goose/Guangdong/1/96) is able to disrupt the PB1c-PB2n interaction.…”
Section: Resultsmentioning
confidence: 99%
“…The polymerase subunit PB1 plays a central role in RdRp assembly [14,18,21], and thus interfaces between PB1 and PA/PB2 could be potential targets for anti-influenza drugs. In-depth analyses have found that it is the N-and C-termini of PB1 that are involved in its interactions with PA and PB2, respectively [22][23][24]. It has been shown previously that a peptide derived from the N-terminal 25 amino acids of PB1 (denoted as PB1 ) can induce the disruption of the PA-PB1 interaction and thus effectively inhibit influenza virus polymerase activity [15,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Controversial reports exist about the domains of PB1 and PB2 required for complex formation (17,30,35,36,40). However, a crystal structure of a PB1 C (residues 678 to 757)-PB2 N (residues 1 to 37) complex was determined recently (40).…”
mentioning
confidence: 99%